Analisis Faktor yang Mempengaruhi Loyalitas Pelanggan Asuransi Kesehatan di Jakarta - Indri Agustianti (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2018)
The purpose of this research is to know the influence of corporate image, customer trust, social bond, customer satisfaction toward health insurance customer loyalty. Respondents in this research is health insurance participants in Jakarta. The method used in this research is a quantitative method with using convenience techniques sampling. The number of respondents 250 individuals. Collected data analyzed the validity and reliability. Research hypothesis tested with Structural Equation Modelling (SEM).